2017
DOI: 10.14336/ad.2017.0607
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Management in the Oldest Old: Improving Outcomes and Tailoring Treatments

Abstract: Ovarian cancer is the most common cause of death from gynecological cancers in developed countries. It is a common disease of older women at or above 63 years upon diagnosis. Thanks to advance in new treatments, mortality from ovarian cancer has declined in developed countries in the last decade. This decline in mortality rate is unevenly distributed across the age-spectrum. While mortality in younger women has decreased 21.7%, for elderly women it has declined only 2.2%. Even if ovarian cancer is clearly a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 57 publications
1
34
0
2
Order By: Relevance
“…The incidence rate of EOC increases with age. Our data together with others' studies showed that advanced age in patients with EOC was associated with short survival duration.- 30,31 Furthermore, in the subgroup analyses, adjuvant CIT was found to be significantly associated with an improved overall survival rate in patients more than 45 years old, but this association was absent in EOC patients who were under the age of 45. This improvement or lack thereof may be explained by the fact that immune alteration is age dependent.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The incidence rate of EOC increases with age. Our data together with others' studies showed that advanced age in patients with EOC was associated with short survival duration.- 30,31 Furthermore, in the subgroup analyses, adjuvant CIT was found to be significantly associated with an improved overall survival rate in patients more than 45 years old, but this association was absent in EOC patients who were under the age of 45. This improvement or lack thereof may be explained by the fact that immune alteration is age dependent.…”
Section: Discussionsupporting
confidence: 70%
“…While mortality in younger women has decreased by 21.7%, said figure was only 2.2% lower for elderly women. 31 Our results revealed that adjuvant CIT achieved favorable clinical outcomes for older patients, suggesting its effectiveness as a treatment for older EOC patients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The lifetime risk of developing ovarian cancer in general population is 1.4 per cent and the mean age of presentation is 64 years, even though his incidence are varied by regions (7). Many factors play major role in the disease development and these includes advance age (8,9), genetics associations (10)(11)(12), early menstruation (13), late menopausal age (14) and hormonal therapy (15). An ovarian tumor mainly originates from its own tissue but some multiple tumors such as colon (16), stomach (17), small intestine (18), pancreas (6), breast (19) and even thyroid cancer (20) can be metastasis to the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime risk of developing ovarian cancer in general population is 1.4 per cent and the mean age of presentation is 64 years, even though its incidence are varied by regions (7). Many factors play major role in the disease development and these includes advance age (8,9), genetics associations (10)(11)(12), early menstruation (13), late menopause (14) and hormonal therapy (15). An ovarian tumors are mainly primary but secondaries from colon (16), stomach (17), small intestine (18), pancreas (6), breast (19) and even thyroid cancer (20) are also common.…”
Section: Introductionmentioning
confidence: 99%